Ответ:
Пошаговое объяснение:
√2 sin (2x+
) + 1 = 0
√2 sin (2x+
) + 1 = -1
sin (2x+
) = ![-\frac{1}{\sqrt{2} } -\frac{1}{\sqrt{2} }](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%20%7D)
sin (2x+
)= ![-\frac{1}{\sqrt{2} } -\frac{1}{\sqrt{2} }](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%20%7D)
sin(
-(2x+
))= ![-\frac{1}{\sqrt{2} } -\frac{1}{\sqrt{2} }](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%20%7D)
2x+
=arcsin (
)
sin(
-2x)= ![-\frac{1}{\sqrt{2} } -\frac{1}{\sqrt{2} }](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B%5Csqrt%7B2%7D%20%7D)
2x+
=arcsin (
) + 2k
, k ∈ Z
- 2x=arcsin (
)
x= -
+ k
, k ∈ Z
- 2x=arcsin (
) + 2k
, k ∈ Z
x=
, k ∈ Z
x=
, k ∈ Z
x=
, k ∈ Z
x=
, k ∈ Z
k ∈ Z
Поблагодари и отметь как лучший ответ пж